(untitled) (Al-Academy, 2024)
The current research explores the identification of digital technologies and the artistic and aesthetic use of the computer, as a digital alternative to traditional Dimmer lighting control devices in contemporary theatrical performances, and the artistic and technical treatments it provides and multiple creative options in light constructions on the physical, artistic and technical levels based on its achieved characteristics. In proposing a digital control device (Dimmer) to become an experimental mediator in achieving the creative hypothesis, which determined the research with a pivotal goal: identifying the technical characteristics of the digital alternative of the Dimmer device in contemporary theatrical lighting, which can be summarized in the following question: How is digital technology employed using a device? The computer is an alternative to traditional control devices in organizing, distributing and shaping theatrical lighting on stage, in a way that is compatible with contemporary digital technology. The research comes within its objective limits stated in its methodological framework, which are: the digital alternative to the digital dimer control device, and the technical treatments it provides in lighting constructions based on its characteristics achieved in the design and distribution of lighting devices on stage. The research included a methodological framework in which the researcher defined the research problem, its importance, the need for it, and its goal, and also defined its terms procedurally. The theoretical framework included two sections: the first section: digital technology in theater, and the second section: the technical work of the digital alternative to dimers. It ended with indicators from the theoretical framework. In the research procedures, the researcher used as a sample of his research the model play (Al-Hussein Now) by director Aqeel Mahdi. The researcher concludes the conclusions of his research, the most important of which are: The digital alternative of the Dimmer is characterized by high flexibility in working, designing and implementing according to the programs that are originally stored in the computer or that are purchased and worked on. 2. Treatment with a digital alternative to the dimer achieves a profit by reducing the material cost, compared to the traditional dimer, in addition to the weight, size, and lifespan, in addition to the time factor.